1959
DOI: 10.1002/aic.690050211
|View full text |Cite
|
Sign up to set email alerts
|

Viscous flow relative to arrays of cylinders

Abstract: The free‐surface model, successfully employed to predict sedimentation, resistance to flow, and viscosity in assemblages of spherical particles, has been extended to the case of flow relative to cylinders. It is shown to be in good agreement with existing data on beds of fibers of various types and flow through bundles of heat‐exchanger tubes for cases where it can reasonably be expected to apply. Close agreement in the dilute range with the only theoretical treatment for flow parallel to a square array of cyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
473
0
6

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 866 publications
(501 citation statements)
references
References 7 publications
11
473
0
6
Order By: Relevance
“…The permeability constant for a highly porous fibrous medium has been derived analytically for flow around a cylinder by Happel [12].…”
Section: δPmentioning
confidence: 99%
See 3 more Smart Citations
“…The permeability constant for a highly porous fibrous medium has been derived analytically for flow around a cylinder by Happel [12].…”
Section: δPmentioning
confidence: 99%
“…The mechanical stress arises from the drag of fluid on the surface of the medium as the fluid flows. The drag also results in the drop of the hydraulic pressure in the direction of the flow [12]. The mechanical stress on the fiber mat increases in the flow direction because the force propagates via the fiber-fiber contacts [23].…”
Section: Modeling Of Permeationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we present a model wherein the foulants are assumed to form a uniform coating that envelops the fibers that make up the membrane, both reducing the available volume of the membrane for transport and increasing the effective diameter of the fibers, as shown in Figure 2. We have previously shown that the permeability of electrospun fiber membranes is reasonably welldescribed by Happel's equation for solidities up to 50-60% [18,29]. The normalized flux can be approximated by the following equation:…”
Section: Conformally Coated Fibers (Ccf) Modelmentioning
confidence: 99%